Comparison of essential oils and secretion structures of Rosa damascena Mill. grown in Iğdır and Isparta (Turkey) - Zuhal Güvenalp; Allahverdi Karaca; Betül Demirci; Gözde Öztürk; Ayşe Civaş; Enes Tekman; Hafize Yuca; Songül Karakaya (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The paper aims to compare the chemical compositions of essential oils and anatomical properties of secretory structures differences between R. damascena which is cultivated in Iğdır and Isparta (EOI1, EOI2, and EOIg). GC/ MS and GC-FID were utilized for essential oils analysis. Nonadecane (31.0%), heneicosane (21.1%), citronellol (16.8%), and 1-nonadecene (6.2%) were primal constituents of EOI1. Nonadecane (29.3%), heneicosane (17.6%), citronellol (18.6%), 1- and nonadecene (5.4%) were primal constituents of EOI2. Heneicosane (15.2%), nonadecane (14.1%), γ-muurolene (13.0%), citronellol (7.8%), and tricosane (8.5%) were primal constituents of EOIg. Both Isparta and Iğdır sepal cross-section anatomies glandular and non-glandular trichomes were observed.